Optical driving, spin initialization and readout of single SiV− centers in a Fabry-Perot resonator - Gregor Bayer; Robert Berghaus; Selene Sachero; Andrea B. Filipovski; Lukas Antoniuk; Niklas Lettner; Richard Waltrich; Marco Klotz; Patrick Maier; Viatcheslav Agafonov; Alexander Kubanek (Communications Physics)
Abstract Large-scale quantum communication networks require quantum repeaters due to the signal attenuation in optical fibers. Ideal quantum repeater nodes efficiently link a quantum memory with photons serving as flying qubits. Color centers in diamond, particularly the negatively charged silicon vacancy center, are promising candidates to establish such nodes. Inefficient connection between the color center’s spin to the optical fiber networks is a major obstacle, that could be resolved by utilizing optical resonators. Here, we couple individual silicon vacancy centers incorporated in a nanodiamond to a hemispherical, stable Fabry-Perot microcavity, achieving Purcell-factors larger than 1. We demonstrate coherent optical driving between ground and excited state with a Rabi-frequency of 330 MHz, all-optical initialization and readout of the electron spin in magnetic fields of up to 3.2 T. Spin initialization within 67 ns with a 80 % fidelity and a lifetime of 350 ns are reached. Our demonstration opens the way to realize quantum repeater applications.